Honesty and comfort levels in mothers when screened for perinatal depression and anxiety. Issue 2 (March 2020) - Forder, Peta M.; Rich, Jane; Harris, Sheree; Chojenta, Catherine; Reilly, Nicole; Austin, Marie-Paule; Loxton, Deborah
Abstract: Purpose: To evaluate the degree of honesty and level of comfort reported by women when questioned about their emotional wellbeing during the perinatal period; to investigate if honesty and comfort are associated with perinatal depression or perinatal anxiety; and to examine the reasons why women may not always respond honestly. Methods: Qualitative and quantitative data from 1597 women from the cross-sectional perinatal mental health substudy (part of the Australian Longitudinal Study on Women's Health) were analysed using a mixed methods approach. Results: When questioned by their health practitioner about their emotional wellbeing in the perinatal period, 20.7% of women indicated they had not always responded honestly. Reasons for not being honest reflected four main themes: normalizing of symptoms/coping; negative perceptions (self-and others); fear of adverse repercussions; and fear of involvement of health services (trust and confidentiality). The 38.9% of women who did not feel comfortable when questioned by their health practitioner about their emotional wellbeing were four times more likely to report perinatal depression (odds ratio = 4.09; 95% confidence interval = 2.55, 6.57) and nearly twice as likely to report perinatal anxiety (odds ratio = 1.90; 95% confidence interval = 1.24, 2.94) than other women. Conclusions: Women who are most likely to need mental health care during the perinatal period are also those least likely to be honest about their mental health. A non-judgemental, open and reassuring approach by clinicians may help to reduce the stigma and fears contributing to lack of honest responses, and improve early diagnosis and treatment of mental health problems.